Психологічні детермінанти внутрішньої мотивації до навчання у студентів технічних спеціальностей - Підбуцька, Ніна Вікторівна; Курявська, Олена Миколаївна (НТУ "ХПІ", 2012)
In the article consistently reveals the problem of the inner motivation for learning, it is importance in educational psychology and special features of the student's age. In the process of the pilot study identified the psychological determinants of internal motivation for learning the students of technical specialities, among which: orientation of the activity on material goods, self-assertion, creative interiorization.
Keywords: соціально-економічні перетворення; процес удосконалення підготовки; мотивація; соціальні потреби